Review of The Men Who Lost Singapore, 1938-1942, by Ronald McCrum - Kankan Xie (Bijdragen tot de taal-, land- en volkenkunde / Journal of the Humanities and Social Sciences of Southeast Asia, 2018)
Britain’s loss of its Southeast Asian colonies during World War Two (WWII), especially the fall of Malaya and Singapore, is a relatively well-studied topic. While existing scholarship has covered the military failure in great detail, researchers have not paid equal attention to the disorganization of the colonial administration, which played a no less important role in the years leading up to the defeat. Based on his meticulous research in British archives, Ronald McCrum has filled the gap by scrutinizing the ‘irresponsible and incompetent’ behaviors of the civilian authorities. He argues that by pursuing different priorities, the colonial government failed to take necessary measures to counter the growing threat of the Japanese. Besides the fact that the British civilian administration was in disarray within itself, their poor relationship with the military also greatly hindered joint efforts to augment the defense against the imminent invasion, which ultimately led to astonishing casualties when the war broke out.